Analisis Quality Of Service Video Streaming Pada Ethernet Over Internet Protocol Dengan Metode Priority Queueing Dan Per Connection Queue - Azmuri Wahyu Azinar; Dian Khoirul Hudalloh (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2016)
There is increasing number of Indonesian people untilizing video streaming application in ther daily life. Video streaming can be used for farious activities such as distant learning, or as a monitoring facility. Public network (internet) has some suscepbtiilities on the scurity of the data being transmitted. To overcome this, Tunneling network technology is used. In QOS video streaming analysis on EOIP protocol the process start with system designing, hardware installation, video server installation of EOIP, PQ method implementation, PCQ methot implementation, data retival end data analisys. In this research, the followings are anallyzed: video streaming QOS (Quality of Service) on EOIP (Ethernet Over Internet Protocol) by means of PQ (Priority Queuing) and PCQ (Per Connection Queue), covering QOS parameter i.e. Delay, Jitter and Throughput. The result show that on the video streaming with PQ(Priority Queuing) and (Per Connection Queue) there is a discrepancy of QoS. PQ method is supportive towards QOS for the highest priority client. This is because streaming server can give priority service for client having the highest priority, so as to have a better QOS. PCQ method is very supportive towards QOS among clients because streaming server can distribute service to several clients doing streaming activity simultaneously.